Trade possibilities and non-tariff barriers to Indo-Pak trade - Nisha Taneja (Indian Council for Research on International Economic Relations (ICRIER), 2007)
This paper aims to identify the bilateral trade possibilities and non-tariff barriers between India and Pakistan. The study shows that there is a large untapped trade potential between the two countries. Using the potential trade approach, the study finds that the export potential from India to Pakistan is to the tune of US 9.5 billion while that from Pakistan to India is US 2.2 billion. Items having export potential from Pakistan are largely in the textile sector while items having export potential from India are predominantly in non-textile sectors. Very few items having export potential from India are on the positive list adopted by Pakistan. At the same time there are several items that India is importing from other countries but not from Pakistan. This indicates that there is a huge information gap on both sides on items that can be imported by India from Pakistan. A working definition of non-tariff barriers adopted in the study included six major categories, namely, quantitative restrictions, trade facilitation and customs procedures, technical barriers to trade and sanitary and phytosanitary measures, financial measures, para-tariff measures and visas. The study was based on an extensive survey conducted in several cities in India and Pakistan. Further, despite the two countries having liberalized their import regimes, Pakistan continues to follow a positive list approach towards Indian imports. The study identifies the ways in which this policy impedes India's exports and recommends the dismantling of the positive list. It also identifies problems related to transportation, custom procedures, rules of origin certification and valuation and suggests measures to address them. The imposition and application of standards in India was perceived as a major non-tariff barrier by Pakistani exporters. The study found that even though the TBT and SPS measures are not discriminatory across trading partners, Pakistani exports to India are surely affected by these. Pakistan has an export interest in textiles and agricultural products which also happen to be sectors where import restrictions/standards are most rigorously applied by India. It also found that due to a restrictive visa regime only selected traders have access to trade-related information. Thus lack of transparency, market imperfections and information asymmetries on both sides raise transaction costs and restrict market access for several other aspiring traders.
Keywords: F1; F13; F5; 330; Trade; Trade policy; non-tariff barriers; South Asia; India Pakistan and International Relations; Internationale Wirtschaft; Nichttarifäre Handelshemmnisse; Außenwirtschaftspolitik; Internationale Wirtschaftsbeziehungen; Indien; Pakistan